Pengembangan E-Modul Pembelajaran Agama Kristen Menggunakan Scaffolding untuk Meningkatkan Kemampuan Metakognitif Komunitas Remaja Kristen Sumba - Nova Nova; I Nyoman Sudana Degeng; Sulton Sulton (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
The aim of this research is to produce an electronic module that uses scaffolding in Christian Instructional for Sumba Christian Adolescence Community, as well as examining the feasibility. The Development Model used is the ADDIE model which completes the steps of Analysis, Design, Development, Implementation, and Evaluation. This product has a material level of 97,5%, the feasibility of instructional design 96,25%, and feasibility of instructional media expert 95%. Additionally, the trial rate based on individual trials is 99,16%, based on small group trials is 96,67%, and based on field trials 94,71% with very decent qualifications and do not need to be revised. In addition, the result of the effectiveness of the use of e-modules into effective qualifications based on pre-test and post-test.